Hierarchically structured electrode materials derived from metal-organic framework/vertical graphene composite for high-performance flexible asymmetric supercapacitors - Mingliang He; Gan Jet Hong Melvin; Mingxi Wang; Wanli Fan; Jingwen Lin; Xiaobo Chen; Keng Xu; Cailei Yuan; Yongyi Zhang; Fei Zhang; Zhipeng Wang (Elsevier Ltd., 2023)
Low conductivity of metal-organic frameworks limits their applications in electrochemical energy storage and conversion. To overcome this shortcoming, we synthesized the zeolitic imidazolate framework-67 on the vertical graphene (VG) surface with abundant defects grown on carbon cloth (ZIF-67-VG-CC). Based on “one-for-two” strategy, the Co₃O₄ nanoparticles (Co3O4-VG-CC) and nanoporous carbon (NC-VG-CC) can be derived from ZIF67-VG-CC via selective pyrolysis in the controlled atmospheres. In the hierarchically structured Co₃O₄ -VG-CC and NC-VG-CC, the Co₃O₄ nanoparticles with a size of 20 nm and N-doped porous carbons were uniformly dispersed on the VG surface, as confirmed by electron microscopies. Both the Co₃O₄ -VG-CC and NC-VG-CC yield high specific capacitance and excellent rate capability. After assembling these two electrodes to make an asymmetric supercapacitor, the Co₃O₄ -VG-CC//NC-VG-CC delivered a maximum energy density of 43.75 Wh/kg at a power density of 5.2 kW/kg as well as excellent cycling stability with 91.5 % specific capacitance retained after 20,000 charge-discharge cycles. All these results should be ascribed to that the VG sheets possess their high electrical conductivity and 3D network structure, and provide the hierarchical supports for the uniform distribution of the ZIF-67-dervied Co₃O₄ nanoparticles and NC materials, which are beneficial to the fast electron and ion transfer in the electrodes.